2000
DOI: 10.1080/110241500447218
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Digital Tympanic, Oral, Axillary, and Rectal Thermometers Compared with Standard Rectal Mercury Thermometers

Abstract: We conclude that electronic rectal temperature measurements are the most accurate. We do not recommend electronic tympanic, oral, or axillary measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 8 publications
4
65
0
Order By: Relevance
“…Thus, measuring core temperature through the tympanic membrane vs. the rectum and esophagus may produce different results. Studies suggest that T TY may underestimate core temperature by 0.3-0.6 °C relative to esophageal or rectal tem perature (Jensen et al, 2000;Roth et al, 1996;Shiraki et al, 1986;Yeo and Scarbough, 1996). However, Newsham et al (2002) have also shown a strong correlation between T TY and rectal temperature.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Thus, measuring core temperature through the tympanic membrane vs. the rectum and esophagus may produce different results. Studies suggest that T TY may underestimate core temperature by 0.3-0.6 °C relative to esophageal or rectal tem perature (Jensen et al, 2000;Roth et al, 1996;Shiraki et al, 1986;Yeo and Scarbough, 1996). However, Newsham et al (2002) have also shown a strong correlation between T TY and rectal temperature.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Before adopting new noninvasive methods of measurement, being quite certain that the new method will give results that agree with older methods and that can be subjected to recognize statistical procedures is important 11 . For this purpose, we performed four different approaches to compare three methods with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Oral and rectal temperatures are the most reliable predictors of core temperature 8,9 . Rectal measurement is assumed to be the clinical standard 10,11 . But measuring fever with oral or rectal route would sometimes be difficult because they are stressful for infants, are time-dependent and require acertain level of practice.…”
mentioning
confidence: 99%
“…3 Common alternatives include oral, aural (tympanic), temporal, and axillary temperature. The validity of these sites in estimating core body temperature has been examined in toddlers, [4][5][6] hospital patients, 7,8 and participants exercising outdoors. 1 However, many of these authors did not validate measurement sites when hyperthermia was exercise induced.…”
Section: Journal Of Athletic Trainingmentioning
confidence: 99%
“…The evidence indicates that RCT is valid and reliable for individuals at rest and while exercising [8][9][10][11][12] and is considered the ''gold standard'' for temperature measurement in hyperthermic athletes. [13][14][15] Despite a reported lag in response time (eg, versus esophageal or pulmonary artery temperature), RCT provides a valid and reliable core temperature measurement in the field for diagnosis and treatment of exertional heat stroke.…”
Section: Journal Of Athletic Trainingmentioning
confidence: 99%